2013
DOI: 10.2131/jts.38.947
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of cadmium-induced chronotoxicity in mice

Abstract: -Biological defense factors show diurnal variations in their expression levels or activities. These variations can induce the different sensitivity to external toxicants of a day. We reported earlier that mice showed clear diurnal variation of cadmium (Cd)-induced toxicity, i.e., chronotoxicity. In this report, we investigated additional new evidences for the cadmium (Cd)-induced chronotoxicity, and considered the mechanisms contributed to this chronotoxicity. Male C57BL/6J mice were injected with CdCl 2 (6.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 32 publications
4
21
1
Order By: Relevance
“…14,15) Measurement of Hepatic Ca (Ca 2+ ) Concentration Liver specimens (0.2-0.3 g each) were digested in 0.5 mL of concentrated nitric acid (60%: Kanto Chemical, Tokyo, Japan) in glass test tubes. The digested samples were held at 80°C for 1 h, with a subsequent gradual increase in temperature (10°C/h) until the sample temperature reached 130°C.…”
Section: Animal Treatmentmentioning
confidence: 99%
“…14,15) Measurement of Hepatic Ca (Ca 2+ ) Concentration Liver specimens (0.2-0.3 g each) were digested in 0.5 mL of concentrated nitric acid (60%: Kanto Chemical, Tokyo, Japan) in glass test tubes. The digested samples were held at 80°C for 1 h, with a subsequent gradual increase in temperature (10°C/h) until the sample temperature reached 130°C.…”
Section: Animal Treatmentmentioning
confidence: 99%
“…Cadmium persists in the human body because it cannot be easily excreted and its concentration increases with age (Ikeda et al, 2004). An epidemiological survey reported that higher intake of cadmium is associated with a higher incidence of renal impairment (Heilmaier et al, 1987;Lee et al, 2013;Miura et al, 2013;Summer et al, 1986;Tokumoto et al, 2014); thus, the health problems caused by cadmium are a global concern.…”
Section: Introductionmentioning
confidence: 99%
“…Y R = 101.64X + 306.31 (R² = 0.99) (1) Y S = 38.539X + 946.76 (R² = 0.87) (2) Y L = 10.183X + 505.63 (R² = 0.91) (3) …where Y R , Y S , and Y L are the Cd concentrations in the roots, stems, and leaves, respectively, and X is the concentration of Cd in the soil.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the high level of Cd accumulation in I. aquatica, plants that grow in contaminated soils are not recommended for human consumption. Cd toxicity can pose direct threats to human health via the food chain, and it can cause disease (e.g., itai-itai disease, cancer), damage to the skeletal system, adverse cardiovascular events, enzyme inhibition, DNA damage in humans [1], and chronic toxicity in animals [2]. An example of the RAPD banding patterns observed in RAPD fingerprinting experiments is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%